Cybrarian (Cyber Librarian) Dalam Rangka Menghadapi Pengguna di Era Net Generation yang Memiliki Gaya Hidup Hedonisme - Fransiska Timoria Samosir (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
Hedonism amid net generation resulting behavior of the next generation has a high level of technology use and consumptive nature that likes to update the latest technology and social media use is high. This resulted in net generation behavioral change. To anticipate these behavioral changes will require librarians to become a partner of the user. Improvement can be done by making the librarian as cybrarian. Establishment of cybrarian is the one way to increase human resources in the library to provide services according to needs of the net generation. This increase can be given the library by providing training and education. A cybrarian will have the ability to visual literacy, digital literacy, ICT literacy, information literacy, and the others. Cybrarian will have the ability to provide knowledge to the net generation, so that the gadget they have to be utilized, particularly those giving a positive effect in improving technological capabilities and user communication.